Growth curves for intracranial volume in normal Asian children fortify management of craniosynostosis. Issue 11 (November 2017) - Kamochi, Hideaki; Sunaga, Ataru; Chi, Daekwan; Asahi, Rintaro; Nakagawa, Shiho; Mori, Masanori; Uda, Hirokazu; Sarukawa, Shunji; Sugawara, Yasushi; Yoshimura, Kotaro
Abstract: Background: Although the charting of normal intracranial volume (ICV) is fundamental for managing craniosynostosis, Asian norms in this regard are unknown. The purpose of this study was to establish a growth curve for ICVs in a large series of normal Asian children, providing reference values to guide corrective surgery. Methods: A total of 124 normal children (male, 63; female, 61) and 41 children diagnosed with craniosynostoses were analyzed. Patients aged 0–8 years presenting to the emergency room and subjected to computed tomography (CT) for head trauma served as the reference cohort. Axial CT head scan data were obtained from radiographic archives at Jichi Medical University. Imaging was done on a Siemens CT scanner (5-mm slice thickness), using a DICOM viewer to measure ICVs. Results: ICVs were plotted against age, and best-fit logarithmic curves for normal subjects were generated, without and with gender stratification. Male and female growth curves were similar in shape but diverged past the age of 1 year (male > female). ICVs of patients with craniosynostoses were plotted to male and female growth curves by disease subset, revealing the following: sagittal synostosis, near normal (or marginally larger); metopic synostosis, below normal; other non-syndromic synostoses (unilateral, bilateral, and lambdoidal) and Crouzon syndrome, near normal; Apert syndrome, above normal; and Pfeiffer syndrome, variable. Conclusion: ICVs of early childhood were investigated in Asian subjects, creating growth curves that set criteria for timing, planning and goalsetting in surgical correction of craniosynostosis.